The level of knowledge, awareness and practice on sunscreen usage among nursing students in Universiti Sains Malaysia, Kelantan - Jana, Nur Anis Syazana (Universiti Sains Malaysia, 2023)
Sunscreen has been proven to prevent our skin from sunburn and skin cancer. However, the application of sunscreen among people is still poor. Thus, high knowledge and practice are essential to all nursing students to educate people in the future. A cross-sectional study was carried out to study the knowledge, awareness and practice on sunscreen usage among nursing students in USM. The questionnaire that used in this study was adapted from study in Indonesia. A total of 112 nursing students in USM who fulfilled the inclusion and exclusion criteria were selected by using randomizer tool. Data collected were statistically analyzed using Statistical Package Social Sciences (SPSS) version 27.0 and Pearson’s Chi-Square test was used for the data analysis. As for the knowledge and practice score, the results show 53 (47.3%) for good knowledge and 43 (38.4%) for good practice respectively. The result also demonstrated that there was an association between the knowledge and practice score (p < 0.05) on sunscreen usage among nursing students. It shows only 31.3% of respondents who have good knowledge and practice score.